2022
DOI: 10.1038/s41467-022-33782-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-centric analysis of short and long read metagenomes reveals uncharacterized microbiome diversity in Southeast Asians

Abstract: Despite extensive efforts to address it, the vastness of uncharacterized ‘dark matter’ microbial genetic diversity can impact short-read sequencing based metagenomic studies. Population-specific biases in genomic reference databases can further compound this problem. Leveraging advances in hybrid assembly (using short and long reads) and Hi-C technologies in a cross-sectional survey, we deeply characterized 109 gut microbiomes from three ethnicities in Singapore to comprehensively reconstruct 4497 medium and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 86 publications
1
38
0
2
Order By: Relevance
“…We further showed that genome recovery was also greatly impacted by these processes, which combined with marker gene beta diversity, demonstrates that the exact number of iterations for these processes has a significant impact on reconstruction, and thus also interpretation, of the microbial communities. Fortunately, results here followed similar patterns with each other, and also in many aspects mirrored published studies comparing different aspects of hybrid assembly across multiple tools and over several iterations 1,2,4,7,10,[12][13][14][15]17,18,22,[26][27][28][29][30][31]37 . However, there is not only substantial methodological variation between published approaches and the performed here, but also biological variation between each dataset which probably precludes the development and application of a universal or standardized approach for applying hybrid metagenomics to microbial communities.…”
Section: Correction and Polishing Affect Gene-and Genome-centric Comm...supporting
confidence: 83%
See 3 more Smart Citations
“…We further showed that genome recovery was also greatly impacted by these processes, which combined with marker gene beta diversity, demonstrates that the exact number of iterations for these processes has a significant impact on reconstruction, and thus also interpretation, of the microbial communities. Fortunately, results here followed similar patterns with each other, and also in many aspects mirrored published studies comparing different aspects of hybrid assembly across multiple tools and over several iterations 1,2,4,7,10,[12][13][14][15]17,18,22,[26][27][28][29][30][31]37 . However, there is not only substantial methodological variation between published approaches and the performed here, but also biological variation between each dataset which probably precludes the development and application of a universal or standardized approach for applying hybrid metagenomics to microbial communities.…”
Section: Correction and Polishing Affect Gene-and Genome-centric Comm...supporting
confidence: 83%
“…A primary goal for many microbial community metagenomic sequencing approaches is to reconstruct high-quality, ideally essentially complete genomes of as many of the members as possible [1][2][3][4][5][6][7][8][9][10]12,13 . Hybrid assembly of microbial metagenomes has already been employed to recover microbial genomes from a variety of ecosystems from waste sludge to human guts, and more [1][2][3][4][5][6][7][8][9][10]12,13 .…”
Section: Automated Bin Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…Identified IS elements were filtered using the following criteria: 1) multiple (minimum of 2 copies) complete copies of the element must be present in at least one genome and 2) the elements must contain identified inverted repeat sequences. To supplement these genomes, we also identified IS elements in hybrid-assembled MAGs from a large human intestinal microbiota study (26). These metagenomes were annotated with Prokka v1.14.6 (90), processed as described above, and then combined with the IS elements identified from the genomes from NCBI Assembly.…”
Section: Methodsmentioning
confidence: 99%